Il movimento comunitario: storia e attualità - Dario, Mariopaolo (Il sogno della farfalla, 2018)
After describing what has led to the development of therapeutic communities, and distinguishing between those based on a social aim and those based on a psychotherapeutic aim, the article focuses on what happened in Italy in particular. The author underlines the role of the anti-psychiatry movement, which led to the exclusion of therapeutic communities from the Italian psychiatry scenario given their therapeutic vocation. For instance, the communities’ therapeutic intent was strongly opposed by those whose only interest was to face the socio-political impact of mental illnesses. Only recently has this therapeutic setting been taken into account again also thanks to the theoretical formulations of Massimo Fagioli. In fact, by unveiling the deepest psychopathological dynamics, these formulations allow not only to orientate the unique relationship occurring within communities towards socio-rehabilitative objectives but also towards more psychotherapeutic objectives. This will make it possible for psychotherapists to aim at a deeper transformation of the entire personality of patients through the development of new psychic, human and social possibilities.